Overview of Hemoglobin and Hematocrit Levels in Stunted Toddlers in the Kajen 1 Community Health Center Working Area - Hidayah, Laela Nurul; Wibowo, Subur (INDOGENIUS, 2025)
Background & Objectives: Stunting is a condition in which a child's growth and development are disrupted due to prolonged malnutrition. Children who experience stunting are 2.7 times more likely to develop anemia. Common characteristics of anemia include decreased hemoglobin levels and decreased hematocrit (Ht) values. Malnutrition accompanied by anemia can lead to growth disorders, reduced cognitive and psychomotor function, and decreased immunity in children. This study aims to determine the hemoglobin and hematocrit levels in stunted toddlers in the working area of the Kajen 1 Community Health Center. Method: The type of research used was descriptive research, with sampling conducted using total purposive sampling. From a population of 27 toddlers, 18 samples of toddlers who met the inclusion and exclusion criteria were taken. Result: The results of hemoglobin level tests using the POCT method and hematocrit tests using the microhematocrit method showed hemoglobin levels above 11.0 g/dl in 100% of cases, normal hematocrit levels in 10 toddlers (56%), and low hematocrit levels in 8 toddlers (44%). with the lowest hematocrit level being 31% and the highest being 39%. Conclusion: Hemoglobin levels in stunted toddlers in the Kajen 1 Community Health Center working area were all normal above 11.0 g/dl, hematocrit levels were normal in 10 toddlers, and hematocrit levels were low in 8 toddlers.